2018
DOI: 10.3390/fishes3040045
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis and Egg Quality in Finfish: Yolk Formation and Other Factors Influencing Female Fertility

Abstract: Egg quality in fishes has been a topic of research in aquaculture and fisheries for decades as it represents an important life history trait and is critical for captive propagation and successful recruitment. A major factor influencing egg quality is proper yolk formation, as most fishes are oviparous and the developing offspring are entirely dependent on stored egg yolk for nutritional sustenance. These maternally derived nutrients consist of proteins, carbohydrates, lipids, vitamins, minerals, and ions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 163 publications
(352 reference statements)
4
59
0
6
Order By: Relevance
“…Estradiol pre-treated eels induced to mature may therefore be more closely resembling naturally maturing eels and arguably, may sequester more appropriate amounts of vitellogenin. Given the links between appropriate yolk formation and egg quality (reviewed in: [52]), and the low quality of eggs produced by standard hypophysation protocols, comparing vitellogenin content in the eggs stripped from E 2 treated fish to that in eggs from SPH only treated fish seems worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol pre-treated eels induced to mature may therefore be more closely resembling naturally maturing eels and arguably, may sequester more appropriate amounts of vitellogenin. Given the links between appropriate yolk formation and egg quality (reviewed in: [52]), and the low quality of eggs produced by standard hypophysation protocols, comparing vitellogenin content in the eggs stripped from E 2 treated fish to that in eggs from SPH only treated fish seems worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…It is similar with the elevated vitellogenin expression in accordance with either gonadal development or reproductive cycle, which has been observed not only in this chondrostean fish group but in other teleost species (Amberg et al, 2010;Zhang et al, 2011a;Hara et al, 2016;Fajkowska et al, 2016). In early works, vitellogenin has been originally thought as a mature female-specific protein since it is the main proteinogenic component of fish yolk, however, a number of subsequent studies have indicated that the transcription of vitellogenin gene is active also in both males and sexually immature fishes (Arukwe and Goksøyr, 2003;Zhang et al, 2005;Reading et al, 2018). Similarly, in this study, Siberian sturgeon males robustly display hepatic vitellogenin transcripts of which expression levels are readily comparable to those observed in females or even higher than in females in a certain life interval.…”
Section: Discussionmentioning
confidence: 84%
“…In a joint "oil droplet and cortical alveoli step," the lipidic accumulation can be massive with time, pushing cortical alveoli to a thin subplasmalemmal strip, as observed in the goodeids Crenichthys baileyi and Empetrichthys latos (Uribe et al, 2012). The emergence and build-up of lipid droplets in most teleosts phenotypically translate what is presently called "oocyte lipidation" (Reading et al, 2018). Like the goldfish, the zebrafish does not display lipid droplets in oocytes, despite accumulating lipids in yolk (Malone & Hisaoka, 1963;Selman, Wallace, Sarka, & Qi, 1993).…”
Section: Discussionmentioning
confidence: 99%